Contract Farming: Linking Farmers to Markets - Arief Daryanto (Business and Entrepreneurial Review, 2006)
Contract farrning in Indonesia is a growing phenomenon. This paper examines the evolution of contract farming, and explores the incentives to engage in contract farming, preferred contract forms and contract performance from the perspective of both lndonesian farmers and contracting firms. Contract farming is characterized by a contract between a farmer and a firm that will process and/or market the farmer's crop. It has been a component of some of the most successful income generating programs for smallholder farmers; it has been a component of various schemes involving agribusiness firms. Smallholders may enter contracts to reduce transaction costs of accessing new markets, borrowing, managing risk, acquiring in formation or increasing employment opportunities. The success of contracts reflects both the contracting environment and management practices. Benefits from contracting accrue to smallholders from improved access to markets, improved technology, better management of risk and opportunities for employment of family members.